Sediment echosounder raw data (Atlas Parasound P70 echosounder entire dataset) of RV SONNE during cruise SO292 - Lindhorst, Sebastian; Betzler, Christian (PANGAEA, 2024)
Atlas Parasound P70 (mk2) echosounder data was recorded during RV SONNE cruise SO292 (ICECARB, 15.05.2022 to 21.06.2022, Queensland Plateau, NE Australia). Data were acquired in parallel to multi-channel seismic surveys and as stand-alone surveys, with cruising speeds of 5.5 and 7 to 8 kn over ground, respectively. The desired primary high frequency (PHF) of the system was set to 18 kHz, the secondary low frequency (SLF) to 4 kHz. The PS70 was operated in single pulse mode with a transducer voltage of 100 V, and a transceiver amplification of 30 to 40 dB. Sound-velocity profiles (SVP) and salinity profiles of the water column were obtained from CTD measurements when available, and by using XSV-02 probes (Lockheed Martin, Sippican Inc.) for underway measurements. Data were stored in the PARASOUND-native format PS3 as well as in the PARASOUND raw-data format ASD. Whereas ASD data contain the complete acquisition range (0 to 2000 m of water depth), data stored in PS3 only record a specific time window (typical 200 ms in length) starting from just above the sea floor and automatically tracked using the mk2 capabilities. Typical sub-seafloor penetration during SO292 was around 10 m on the top of the carbonate banks (water depth around 50-60 m), almost 0 m at steep- and/or lithified parts of the platform slopes, and 80 to >140 m in the drift sediments surrounding the platforms.
Keywords: carbonate banks; Queensland Plateau; Slope